Pengembangan Fitur Lanjutan Pada Aplikasi Manajemen Personal Individual Berbasis Mobile Android - Billy Prestone Mahulae; Yohana Tri Widayati; Satrio Agung Prakoso (STMIK Banjarbaru, 2025)
The rapid development of technology and personal management challenges among Indonesian youth require an integrated solution to manage both finances and time. This study develops advanced features on the Individual Personal Management Application (AMPI) for Android using the waterfall method, clean MVVM architecture, Coin dependency injection, and Firebase integration for authentication and data storage. A user needs analysis through an online questionnaire with 50 respondents showed a high interest in an integrated application with reminders, data visualization, task prioritization, and secure data storage. The system is designed using use case, activity, sequence, and class diagrams to support account, financial, and time management. Black-box testing confirmed that all features function as designed. The results demonstrate that AMPI effectively assists users, especially young people, in tracking daily transactions, managing schedules, and monitoring productivity and financial conditions.Keywords: Personal Management Application; Android; Financial Management; Time Management; FirebaseAbstrakPerkembangan teknologi dan tantangan manajemen personal pada generasi muda Indonesia menuntut solusi aplikasi yang dapat mengelola keuangan dan waktu secara terintegrasi. Penelitian ini mengembangkan fitur lanjutan pada Aplikasi Manajemen Personal Individual (AMPI) berbasis Android menggunakan metode waterfall, arsitektur MVVM clean, Koin dependen injeksi, serta integrasi Firebase untuk autentikasi dan penyimpanan data. Analisis kebutuhan pengguna melalui kuesioner daring pada 50 responden menunjukkan minat tinggi terhadap aplikasi ter-integrasi dengan fitur mengingat, visualisasi data, prioritas tugas, dan penyimpanan data aman. Sistem dirancang menggunakan use case, aktivitas, sequence, dan class diagram untuk mendukung manajemen akun, keuangan, dan waktu. Pengujian black-box menunjukkan seluruh fitur berfungsi sesuai rancangan. Hasil penelitian menunjukkan AMPI efektif membantu pengguna, khususnya generasi muda, dalam mencatat transaksi harian, mengatur jadwal, serta memantau produktivitas dan kondisi keuangan.